A Chloroplast COR413 Protein From Physcomitrella patens Is Required for Growth Regulation Under High Light and ABA Responses - Ruibal, Cecilia; Castro, Alexandra; Fleitas, Andrea L.; Quezada, Jorge; Quero, Gastón; Vidal, Sabina (Frontiers in Plant Science, 2020)
COR413 genes belong to a poorly characterized group of plant-specific cold-regulated genes initially identified as part of the transcriptional activation machinery of plants during cold acclimation. They encode multispanning transmembrane proteins predicted to target the plasma membrane or the chloroplast inner membrane. Despite being ubiquitous throughout the plant kingdom, little is known about their biological function. In this study, we used reverse genetics to investigate the relevance of a predicted chloroplast localized COR413 protein (PpCOR413im) from the moss Physcomitrella patens in developmental and abiotic stress responses. Expression of PpCOR413im was strongly induced by abscisic acid (ABA) and by various environmental stimuli, including low temperature, hyperosmosis, salinity and high light. In vivo subcellular localization of PpCOR413im-GFP fusion protein revealed that this protein is localized in chloroplasts, confirming the in silico predictions. Loss-of-function mutants of PpCOR413im exhibited growth and developmental alterations such as growth retardation, reduced caulonema formation and hypersensitivity to ABA. Mutants also displayed altered photochemistry under various abiotic stresses, including dehydration and low temperature, and exhibited a dramatic growth inhibition upon exposure to high light. Disruption of PpCOR413im also caused altered chloroplast ultrastructure, increased ROS accumulation, and enhanced starch and sucrose levels under high light or after ABA treatment. In addition, loss of PpCOR413im affected both nuclear and chloroplast gene expression in response to ABA and high light, suggesting a role for this gene downstream of ABA in the regulation of growth and environmental stress responses. Developmental alterations exhibited by PpCOR413im knockout mutants had remarkable similarities to those exhibited by hxk1, a mutant lacking a major chloroplastic hexokinase, an enzyme involved in energy homeostasis. Based on these findings, we propose that PpCOR413im is involved in coordinating energy metabolism with ABA-mediated growth and developmental responses.